2004
DOI: 10.3310/hta8290
|View full text |Cite
|
Sign up to set email alerts
|

VenUS I: a randomised controlled trial of two types of bandage for treating venous leg ulcers

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 47 publications
3
105
0
Order By: Relevance
“…This study was conducted in the UK where there is likely to be greater experience with 4LB. 52 There was no difference in generic and disease-specific quality of life between the two groups. Metaanalysis of four trials suggested a higher probability of healing with 4LB but there was significant heterogeneity reducing the certainty of the effect.…”
Section: Multicomponent Systems Incorporating Elastic Bandage (4lb) Vmentioning
confidence: 84%
See 1 more Smart Citation
“…This study was conducted in the UK where there is likely to be greater experience with 4LB. 52 There was no difference in generic and disease-specific quality of life between the two groups. Metaanalysis of four trials suggested a higher probability of healing with 4LB but there was significant heterogeneity reducing the certainty of the effect.…”
Section: Multicomponent Systems Incorporating Elastic Bandage (4lb) Vmentioning
confidence: 84%
“…The 4LB can sustain high pressure for a considerable time thus allowing for a weekly change of dressings. 52 Short stretch inelastic compression bandages (SSB) are widely used in Europe and Australasia. These consist of orthopaedic wool, one or two SSBs and sometimes a retaining layer (eg cohesive bandage or tubular device).…”
Section: Multicomponent Systems Incorporating Elastic Bandage (4lb) Vmentioning
confidence: 99%
“…Trial data suggests that 70% of patients with uncomplicated venous leg ulceration who receive high compression therapy will heal within six months (60,62). Patients who do not receive this treatment will be unlikely to heal but will still require similar (if not greater) levels of nursing time and dressings.…”
Section: Resultsmentioning
confidence: 99%
“…This collaboration has resulted in NIHR-and Medical Research Council-funded wounds research and particularly randomised controlled trials (RCTs), with Leeds always being one of the most successful recruiting centres. [18][19][20][21] An implicit aim of this research programme was therefore to capitalise on this track record and explore how it could be used to promote much wider collection of data and research involvement of staff beyond those working in the specialist service. An overarching principle was also to ensure that the research that we carry out is of value nationally as well as locally.…”
Section: Local Contextmentioning
confidence: 99%